Implementation of integral control state feedback controller for coupled tank liquid level system - Khairul Anwar, Mat Salim (2008)
This project presents the design of Integral Control State Feedback Controller to implement it at Coupled Tank Liquid Level System. By using feedback it control the liquid level in the coupled tank as required and also to understand the habit and effectiveness of Integral Control State Feedback Controller. This coupled tank is using second order system. The Integral Control State Feedback Controller is designed using pole placement method. The DAQ card is been used to interfacing between hardware and software. The software that been used are Visual Basic 6.0 (VB 6) and MATLAB.